CRONE Body Control with a Pneumatic Self-leveling Suspension System - Bouvin, Jean-Louis; Moreau, Xavier; Benine-Neto, André; Hernette, Vincent; Serrier, Pascal; Oustaloup, Alain (Journal of Applied Nonlinear Dynamics, 2026)
This paper deals with vehicle body control under driver inputs through a pneumatic system using the CRONE approach and follows the objective of vehicle level control through the same system. A comparison between this active system and a passive metallic suspension equipping a Citroën C4 Picasso is presented after modeling the pneumatic (leveling) system of a quarter vehicle model with two degrees-of-freedom. Results show an excellent body control as well as, by using the CRONE approach, a robustness of the stability-degree.